2015
DOI: 10.1590/s1806-92902015001100001
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic stabilization of agronomic traits in Panicum maximum (Jacq.) hybrids

Abstract: -The objective of this study was to evaluate the genotypic stability of agronomic traits in hybrids of Panicum maximum. Hybrids originating from the crosses between two sexual parents and cultivars Mombasa and Tanzania were evaluated in an incomplete-block design. Evaluated traits were total dry matter, leaf dry matter, stem dry matter, percentage of leaves, and leaf:stem ratio. These traits were evaluated in six harvests. Overall, higher repeatability was observed for the traits total dry matter and leaf dry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…2, through ANOVA and Principal Component Correlation (PCCor) methods, respectively. ANOVA consistently came up with the lowest estimates while PCCor the highest, similar to other reports (Martuscello et al, 2007, Lédo et al, 2008, Braz, Fonseca, Jank, Cruz, & Martuscello, 2015. The magnitude of the estimates in Exp.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…2, through ANOVA and Principal Component Correlation (PCCor) methods, respectively. ANOVA consistently came up with the lowest estimates while PCCor the highest, similar to other reports (Martuscello et al, 2007, Lédo et al, 2008, Braz, Fonseca, Jank, Cruz, & Martuscello, 2015. The magnitude of the estimates in Exp.…”
Section: Resultssupporting
confidence: 89%
“…This may be because harvest 3 was done at the end of the rainy season, harvest 4 in the dry season, and harvest 5 at the end of the dry season. Both, Braz, Fonseca, Jank, Cruz, and Martuscello (2015) and Martucscello et al (2015) also reported similar results, in which dry season harvests decrease the repeatability coefficient estimates. In Exp.…”
Section: Resultsmentioning
confidence: 58%
“…The repeatability estimates for fruit weight ranged from 0.29 to 0.45, in Padre Bernardo population, and from 0.51 to 0.61 in the municipality of Goiás population, by the analysis of variance, and by the principal component correlation methods, respectively. The analysis of variance consistently came up with the lowest estimates, while the principal component covariance, with the highest ones, similarly to other reports (Martuscello et al, 2007;Lédo et al, 2008;Braz et al, 2015;Fernandes et al, 2017).…”
Section: Resultssupporting
confidence: 88%
“…Genotypic stabilization studies are also important tools in the evaluation of perennial crops, since during the first harvests, when the plants are still young, a low expression of genes which are important for critical characteristics in the productive phase may occur (Pereira et al, 2002) and thus jeopardize the evaluation process. In addition, the establishment of forages in the field and the change in management in early phases of the research may also result in differential expression of genes that modify the productive response and lead to errors in the evaluation process (Braz et al, 2015a).…”
Section: Researchmentioning
confidence: 99%
“…We believe that after the first harvests (1 and 2) and the harvests of the first dry season (3 and 4), plants were already in a condition of more advanced physiological maturity or with full establishment of root system and aerial part, which led to greater uniformity of the response throughout successive defoliations. These conditions may represent the full expression of genes responsible for yield characteristics, so desired in the productive phase of forage plants, as discussed by Pereira et al (2002) and Braz et al (2015a).…”
Section: S%mentioning
confidence: 99%